Effect of introducing Lamarine Saldonum into the diets of cows during dry period and period of lactation on their productivity and reproductive ability - N. A. Shemuranova; N. A. Garifullina (Аграрная наука Евро-Северо-Востока)
The article presents the data on the effect of the Lamarin Saldonum additive on reproductive function and milk productivity of cows when used in different periods: 30 days and 60 days before calving (groups S1 and S2), beginning from the day of calving (group S3) compared with the control (group C4). Highly productive black and white Holstein breed cows were used in the experiment. The additive was fed at a dose of 0.4 g per 1 kg of live weight during 60 days. It was found that S2 group had significantly shorter duration of pregnancy than S1 and C4 groups by 6.2 and 8.2 days, respectively, remaining within the limits of the physiological norm. The shortest indifference-period compared to C4 was observed in groups S1 and S3, the significant difference being 15.25 % and 18.39 %, respectively. The least number of days from calving to fruitful insemination was recorded in group S1, compared to control the statistically significant differences were 37.16 %, compared to groups S2 and S3 – 28.82 % and 27.67 %, which reliably reduced the period of infertility by 57.33 % relative to the values of group C4, as well by 47.90 % and 46.49 % relative to the indicators of groups S2 and S3. The highest average daily milk yields were recorded in group S1: in the first month of lactation, the difference with groups S2, S3 and C4 was 5.74 %, 14.01 % and 17.06 % (psecond (at p0.05), 14.53 %, 16.52 %, 15.19 %, in the third 9.57 % (p0.05), 13.06 %, 10.94 % (p0.05), in the first 100 days of lactation 11.90 %, 16.86 % (p0.05) and 13.28 % (p0.01), respectively. Thus, the most optimal scheme of application of Lamarin Saldonum for stimulation of reproductive function and milk productivity of cows is 30 days before the expected calving.